Molecular identification and characterisation of rodent- and shrew-borne Hantaviruses - Ithete, Ndapewa Laudika (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Pathology. Medical Virology))--University of Stellenbosch, 2010.